Cognitive Sub-Band Scheduling and Link Adaptation for 5G URLLC - Khan, Jihas; Jacob, Lillykutty (IEEE transactions on cognitive communications and networking, 2021)
Link adaptation for downlink 5G ultra-reliable low latency communication (URLLC) is quite challenging. While reduced feedback schemes for link adaptation are crucial to achieve high spectral efficiency, accuracy of sub-band channel quality indicator (CQI) reports is more critical in 5G URLLC because of the ultra-high reliability and efficient resource utilization requirements. The existing differential feedback mechanism cannot reconstruct sub-band CQIs at the BS exactly. In this paper, existing differential feedback mechanism for link adaptation is first investigated using analytical and simulation models to verify its limitations in reconstructing the sub-band CQIs and to study its impact on URLLC reliability and resource utilization efficiency. Then a cognitive link adaptation using a controlled differential feedback scheme for sub-band CQIs is proposed based on the investigations. Extensive simulation results are provided to show the superior performance of the proposed cognitive solution and to illustrate the theoretical analysis.